Reproductive Health and Nutritional Status of Girl Students in an Urban Area of Bangladesh (Ibrahim Medical College Journal, 2009)
Objectives: To assess status of reproductive health and nutrition amongst girls attending high school in an urban area of Bangladesh. Methods: This cross sectional descriptive study was conducted in four selected girl's high schools. A structured pre-tested questionnaire and a checklist were used to collect data through face-to-face interview and anthropometry. Results: A total of 360 adolescents girls were interviewed. The mean age at menarche of the respondents was found to be 12.4 years. More than half (54.2%) of the respondents were malnourished (BMI < 18.5). More than four-fifths (83%) were found to be suffering from reproductive health problems during or after menstruation. The most common complain (60%) disclosed by the adolescent girls was dysmenorrhoea. Majority (300) of the respondents acknowledged practicing unhygienic protective measures during menstruation. Conclusion: More than half of the adolescents were malnourished, practiced unhygienic protective measures during menstruation and disclosed different types of reproductive health complaints. Findings of the study strongly recommend that adolescent girls of urban Bangladesh need proper and appropriate management of their reproductive health problems. Ibrahim Med. Coll. J. 2008; 2(1): 9-11 Key words: Nutritional Status, Reproductive Health, Adolescence.   doi: 10.3329/imcj.v2i1.2924